(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Environmental ethics found for mindfulness, sprang from environmental emergency. Environmental concerns and issues related with it influence people over the globe, the universe. The explanation behind the quick emergency is because of the absence of unawareness with respect to the insurance of environment. As people have moved toward becoming self-centered, just not very many find a way to make the environment spotless and green. In the course of recent decades we have seen a slow increment in the quantity of writers writing about issues identified with environmental concerns. Yet, to the extent scholarly field is worried, there is broad mindfulness towards ecological worries through the ongoing scholarly hypotheses like Ecocriticism .Nature and Literature have constantly shared a cozy relationship, as it is prove in progress of literature. Literature is notable for reflecting contemporary issues and it is this feeling of concern and its refection in literature that has offered ascend to another branch of literary theory, to be specific Ecocriticism. Ecocriticism is an approach of abstract feedback that means to examine the association between Ecology and Literature. This paper looks at the Ecological Concern in Ruskin Bond chosen short stories.